LO72: Assessing non-technical skills in prehospital ad hoc team resuscitation. (May 2019) - Evans, J.; Lingard, D.; Peddle, D.; Slack, M.
Abstract : Introduction : Successful resuscitation in the ED cannot occur without a viable patient, and in many cases patient viability is dependent upon optimal prehospital resuscitation performed by ad hoc teams formed in real time. Currently, little is known about the cognitive and interpersonal skills, or non-technical skills, that are essential for effective team collaboration under these conditions. We have completed a scoping review to provide a state of the literature and develop a taxonomy of the non-technical skills pertinent to ad hoc teams in prehospital settings.Methods : Our scoping review searched four databases (EMBASE, Medline, Cinahl, and Psychinfo) for articles related to resuscitation in acute care settings. No date criteria were applied, but only full text articles written in English were included. Articles underwent two-reviewer title & abstract screening, full text screening, and analysis. A quality review asked three questions: Are keywords defined? Is the article well-situated within the existing literature? Does the article contribute back to the existing body of knowledge? Although statistical analyses are not appropriate for this scoping review, analysis included a descriptive-analytical framework for organizing data.Results : Of 6932 screened articles, 38 were included in analysis, five articles examined prehospital teams, and one addressed the ad hoc nature of these teams. Only one of these articles met our three quality criteria. Nevertheless, our analysis suggests a rudimentary taxonomy whereby the primary objective of a team leader is to overcome this barrier by facilitating the development of optimal team situational awareness, fostered through timely and accurate briefings with closed-loop communication.Conclusion : This scoping review has identified that non-technical skills pertaining to resuscitation in acute care settings are becoming a widely examined phenomenon; however, few studies contribute in any meaningful way to our understanding of how non-technical skills training can be tailored to those performing as members of ad hoc prehospital resuscitation teams. As the need for interprofessional training is becoming more pressing, we anticipate this review will provide essential guidance for future inquiry as well as design for both educational models and organizational systems-based interventions.